Environmental Isotopes as Indicators for Ground Water Recharge to Fractured Granite - Ofterdinger, U.S.; Balderer, Werner; Loew, S; Renard, Philippe (My University, 2004)
To assess the contribution of accumulated winter precipitation and glacial meltwater to the recharge of deep ground water flow systems in fracture crystalline rocks, measurements of environmental isotope ratios, hydrochemical composition, and in situ parameters of ground water were performed in a deep tunnel. The measurements demonstrate the significance of these ground water recharge components for deep ground water flow systems in fractured granites of a high alpine catchment in the Central Alps, Switzerland. Hydrochemical and in situ parameters, as well as δ18O in ground water samples collected in the tunnel, show only small temporal variations. The precipitation record of δ18O shows seasonal variations of ~14‰ and a decrease of 0.23‰ ±0.03‰ per 100 m elevation gain. δ2H and δ18O in precipitation are well correlated and plot close to the meteoric water line, as well as δ2H and δ18O in ground water samples, reflecting the meteoric origin of the latter. The depletion of 18O in ground water compared to 18O content in precipitation during the ground water recharge period indicates significant contributions from accumulated depleted winter precipitation to ground water recharge. The hydrochemical composition of the encountered ground water, Na-Ca-HCO3-SO4(-F), reflects an evolution of the ground water along the flowpath through the granite body. Observed tritium concentrations in ground water range from 2.6 to 16.6 TU, with the lowest values associated with a local negative temperature anomaly and anomalous depleted 18O in ground water. This demonstrates the effect of local ground water recharge from meltwater of submodern glacial ice. Such localized recharge from glaciated areas occurs along preferential flowpaths within the granite body that are mainly controlled by observed hydraulic active shear fractures and cataclastic faults.